2021
DOI: 10.3390/data6060055
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Algorithms to Knowledge Extraction from Time Series Data: A Review

Abstract: To predict the future behavior of a system, we can exploit the information collected in the past, trying to identify recurring structures in what happened to predict what could happen, if the same structures repeat themselves in the future as well. A time series represents a time sequence of numerical values observed in the past at a measurable variable. The values are sampled at equidistant time intervals, according to an appropriate granular frequency, such as the day, week, or month, and measured according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 179 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…The input data for the model were carried out from data-sheet of materials manufacturers or calculated with models published in scientific literature. 12,33 36…”
Section: Methodsmentioning
confidence: 99%
“…The input data for the model were carried out from data-sheet of materials manufacturers or calculated with models published in scientific literature. 12,33 36…”
Section: Methodsmentioning
confidence: 99%
“…Future work in this area should focus more on the realization of the simulation on both edge and fog platforms, as well as on the translation to digital farm solutions such as mobile and web apps for local farmers who, in most cases, could not afford the high cost of sensors and hardware installation on their farms. Readers are referred to the literature [31,83,[129][130][131][132][133] for more details about unsupervised learning. The system made use of data from soil moisture content, air temperature, and leaf wetness and compares it with predetermined threshold values of various soil and specific crops to guide irrigation decisions.…”
Section: Adaptive Neuro-fuzzy Inference System (Anfis)mentioning
confidence: 99%
“…Among these multiple DL frameworks, due to parameter efficiency and spatial invariance property, CNN has gained adoption for many problems, including time series [18]. Further, Wang et al [19] and Yang et al [20] demonstrated that encoding time series as images using Gramian Angular Field (GAF) and Markov Transition Fields (MTF) for CNNs leads to superior performance and in the identification of patterns not found in the one-dimensional sequence methods.…”
Section: Introductionmentioning
confidence: 99%